(untitled) (Altre Modernità, 2010)
The essay addresses two quite complex issues. The first one is the virulence of the hostility toward gay men that the AIDS pandemic has released: this is the backdrop against which Jarman’s extended elaboration and mourning for his own death is performed, after his diagnosis as body-positive in 1986. The second issue links to the open question of public mourning and its relation to AIDS in the early 90s, when the AIDS epidemic is not at its height, but it is certainly more visible than before, and many artists register the impact of the new sensibility this medical and social emergency actually moulds. Considering a specific time span (the 90s) and focusing mostly on cinema a strategic, privileged arena where gay cultures resist to social and cultural sanctions, this work elaborates on how AIDS as a deathly social and cultural destiny has suggested strategies of mournings that introduce new artistic practices. The analysis is specifically focused on Derek Jarman’s last works, culminating in the film Blue (1993).